How do different testing procedures affect the rheological properties of cement paste?. (November 2020) - Ley-Hernández, Aida Margarita; Feys, Dimitri; Kumar, Aditya
Abstract: Rheological properties of cement-based materials are shear- and time dependent due to the chemical and physical particle bonding. Proper characterization of these properties is necessary to predict the behavior of concrete over time. Often, results on rheological measurements are dependent on different preparation conditions, testing procedures and measuring instruments employed. This paper explores how changes in the testing procedure impact the rheological properties of cement pastes with different superplasticizers. Three procedures with a different shear rate profile were repeatedly imposed. The last shearing for each procedure step was identical, imposing the reference state. The results indicate that the time-evolution of the rheological properties is strongly dependent on the employed procedure. It is hypothesized that, at low imposed shear rates, dissolution and precipitation of hydration products is accelerated, creating a stronger internal structure. As a result, the imposition of a reference state does not guarantee full elimination of shear history.